Contextualizing openness situating open science - Chan, Leslie 1959-; Okune, Angela; Hillyer, Rebecca; Albornoz, Denisse; Posada, Alejandro (Perspectives on open access, 2019)
"An important part of identifying the structural, technical, policy and cultural contexts for Open Science in the Global South is recognizing the plurality and diversity in the framing and meanings of "openness." This volume brings together contributions from the twelve projects that form the Open and Collaborative Science in Development Network (OCSDN), and is organized along four themes: Defining Open Science in Development, Governing Open Science, Negotiating Open Science, and Expanding Open Science for Social Transformation. The collective goal of this volume is to identify examples and reflections that illustrate how opportunities and challenges posed by openness vary across regions, and to identify key differences between actors, institutions, infrastructure and governance of knowledge-based resources in diverse settings. The volume will contribute to and expand upon the literature on "openness," which has largely been written from the standpoint of the Global North. Challenging the asymmetry of global knowledge production and access is central to understanding the growing movement towards Open Science and what it may mean for development thinking and practices. The intent is to further stimulate research and debates on how best to collectively design a knowledge system that is open and equitable for all."--